2012
DOI: 10.5395/rde.2012.37.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic management of a C-shaped maxillary first molar with three independent buccal root canals by using cone-beam computed tomography

Abstract: The aim of this study was to present a method for endodontic management of a maxillary first molar with unusual C-shaped morphology of the buccal root verified by cone-beam computed tomography (CBCT) images. This rare anatomical variation was confirmed using CBCT, and nonsurgical endodontic treatment was performed by meticulous evaluation of the pulpal floor. Posttreatment image revealed 3 independent canals in the buccal root obturated efficiently to the accepted lengths in all 3 canals. Our study describes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Since the first report by Cooke and Cox in 1979 [ 1 ], many investigators have evaluated the root canal anatomy of mandibular second molars. The prevalence of C-shaped canals has been reported to vary depending on the population and ethnic group [ 1 4 7 10 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ]. The mandibular second molars in Asian populations have shown a high prevalence of C-shaped canals in many studies [ 6 18 20 25 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report by Cooke and Cox in 1979 [ 1 ], many investigators have evaluated the root canal anatomy of mandibular second molars. The prevalence of C-shaped canals has been reported to vary depending on the population and ethnic group [ 1 4 7 10 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ]. The mandibular second molars in Asian populations have shown a high prevalence of C-shaped canals in many studies [ 6 18 20 25 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…dobivanje visoko detaljiziranih informacija o morfologiji i za točnu topografiju sustava korijenskog kanala, iako treba imati na umu da se ta tehnologija upotrebljava samo ako dodatni nalazi opravdavaju izlaganje zračenju (13,14).…”
Section: Resultsunclassified
“…Cone-beam computed tomography has emerged as a valuable tool for acquiring highly detailed information on morphology and exact topography of the root canal system, although it should be kept in mind that this technique should only be utilized when it is associated with additional benefits that justify the exposure dose (13,14). We must highlight the importance of the axial slices for defining the canal configuration as C-shaped because, although conventional radiograph is commonly used, it does not provide sufficient information on more complex cases that challenge the inherent two-dimensionality of these systems (8,11).…”
Section: 3mentioning
confidence: 99%
“…15 An operating microscope enhances visualization of canal orifices. 16 Nevertheless, the lower two-thirds of the pulp canal is difficult to assess from the morphology of the cervical third in mandibular premolars with anomalous pulp canal configuration. 14 Yu et al reported a high probability of pulp canal variations in the middle or apical third of mandibular premolar roots and suggested that most mandibular premolars have an oval cross-sectional morphology in the cervical third.…”
Section: Discussionmentioning
confidence: 99%
“… 17 CBCT can provide valuable information for assessing such complex morphology. 16 , 18 However, its use in endodontics has been limited to selected cases in which intraoral radiographs were unsatisfactory for treatment planning. 19 , 20 In the present study, CBCT revealed a fourth canal and 3D modeling of the tooth anatomy provided information about both the internal and the external morphology of the root, enabling preoperative evaluation and facilitating treatment.…”
Section: Discussionmentioning
confidence: 99%